(untitled) (Journal of Bio-Science, 2011)
Context: The pH of the in vitro germination medium is the important factor controlling pollen germination and pollen tube development in different plant species Objectives: The aim of the present study was to assess the effect of pH levels of germination medium on the germinability 14 species of cucurbit. Materials and Methods: In vitro pollen germination of 14 cucurbit species was examined at five different levels of pH using Brewbaker and Kwack’s medium. The pH of the medium was adjusted to 7.0, 7.5, 8.0, 8.5 and 9.0 by using a digital pH meter with the help of 0.1 N HCl and 0.1 N NaOH. In vitro pollen germination was tested using sitting drop culture technique. Five sitting drop cultures of pollen grains of five different pH for each species were raised on five different microslides. Then the slides were placed in a humidity chamber and incubated at 22 ± 2 °C for 1 to 2 hrs. All the cultures were fixed by adding a drop of a 1-2% acetocarmine before start scoring and the germinated and non-germinated pollen grains were scored using a microscope. Results: The pollen germination rate was higher in increased pH level in most of the cucurbit species studied and at 9.0 pH the maximum germination was observed in pumpkin (98%), snake gourd (98%), ridge gourd (96%), pointed gourd (89%), cucumber (98%), bitter gourd (96%), sweet gourd (98%) and sponge gourd (93%). The highest percentage of germination was observed in bottle gourd (98%) cucumber short (96%), watermelon (98%), muskmelon (97%) and ivy gourd (87%) at 8.5 pH level. The only cucurbit species wax gourd showed highest germination (97%) at the lower pH level of 7.5. Analysis of variance for the 14 cucurbits at five different pH levels showed that the differences between the germination rates of pollen grains of 14 cucurbit species at different pH level were highly significant (F=12.49, P<0.001, at 13/52 df). Conclusion: In most of the investigated cucurbit species pH level 8.5 to 9.0 was found optimum for the highest number of in vitro pollen germination, while wax gourd responded maximum pollen germination at pH 7.5. Key words: cucurbit; pollen; germination; pH. DOI: 10.3329/jbs.v17i0.7120 J. bio-sci. 17: 129-133, 2009